Finite Element Modelling of Wave Propagation in Highly Scattering Materials - Van,Pamel A; Huthwaite,P; Brett,CR; Lowe,MJS (American Institute of Physics (AIP), 2015)
Ultrasonic inspection of highly scattering materials presents challenges for industry. This article describes a Finite Element modelling methodology to simulate wave propagation within polycrystalline materials. Concerns are answered regarding its required mesh sampling and ability to capture the complex scattering physics. It is shown that grain scattering phenomena are closely reproduced across a range of scattering regimes. The procedure is subsequently applied to investigate the optimal configuration of an array inspecting such a material. It is found that in certain situations, separating emitter and receiver can be advantageous as this reduces the received backscatter.